Issues in Insolvency of Enterprise Groups. Issue 1 (June 2019) - Garg, Risham
Insolvency of enterprise groups has long remained an enigmatic and untouched issue in the realm of international insolvency law. Recently, the Working Group V of United Nations Commission on International Trade Law (UNCITRAL WG V) has taken up the onerous task to fill this void and to draft an instrument/model law to govern international aspects of insolvency resolution of enterprise groups (two or more enterprises that are interconnected by control or significant ownership) 2 including obligations of directors of enterprise group companies for acts done in the 'twilight zone'. This article attempts to introduce and outline certain key issues relating to insolvency resolution of enterprise group companies and discuss a few of them, reserving a comprehensive discussion shared in subsequent papers.